Analisis Harga Pokok Produksi Usahatani Bawang Putih Berdasarkan Luas Lahan DesaFatuneno Kabupaten Timor Tengah Utara - Marsela Kono; Boanerges Putra Sipayung (AGRIMOR, 2020)
Calculation of the cost of production is important to know the price conditions of garlic.This study aims to analize cost garlic farmers production and to know revenue cost ratio in Fatuneno Village North Central Timor Regency. This study was conducted in Fatuneno from April 2019 to August 2019. The method used in this research is quantitative descriptive method. The analysis shows that the cost of production is based on the smallest area of land Rp. 78.971/kg, and the largest land area Rp.28.921/kg, this is higher than the calculation of farmers for the smallest land area Rp. 20.301 and the largest area is Rp.13.242. The profitability ratio of garlic farming in Fatuneno village with the smallest land area is 1.48 and the largest land area is 2.27, with an average R / C ratio of 1.76.